In situ nanomechanical behavior and self-healing response of polymeric multilayer thin films. (22nd November 2017) - Humood, Mohammad; Polychronopoulou, Kyriaki; Song, Yixuan; Grunlan, Jaime C.; Polycarpou, Andreas A.
Abstract: Self-healing of mechanical damages was triggered in polymeric multilayer films of polyethylenimine/polyacrylic acid (PEI/PAA) by exposure to high humidity conditions such as immersion in deionized (DI) water. In situ wet nanoindentation was carried out to demonstrate the swelling behavior of thin films in high humidity. Once immersed in DI water, the film became softer, where roughness, modulus and hardness were reduced by about 100%. Once the film was dried, its mechanical properties were restored but not its morphology. Heating was found to be required to promote the evaporation of immobilized water molecules, which bonds with the polymer once being immersed in DI water. When heating above glass transition temperature (Tg) was introduced, a formation of new bonding between both PEI and PAA took place leading to the formation of new topographical features similar to the as-deposited film. This reconstruction under high temperature (HT) was accompanied by more than 50% increase in the mechanical properties, which were measured using in situ HT nanoindentation. Multiple stimuli were required to achieve complete self-healing. The molecular mechanisms of these stimuli were determined using X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR). Graphical abstract: Highlights: Polymer self-healing studied by in-situ wet and high temperature nanoindentation. Mechanical properties were influenced by changes in the free volume of the film. Complete self-healing of polymeric films required multiple stimuli. Water can be immobilized on the surface roughness or diffused into the film.